2020
DOI: 10.1111/bju.15312
|View full text |Cite
|
Sign up to set email alerts
|

Toward improved endoscopic examination of urinary stones: a concordance study between endoscopic digital pictures vs microscopy

Abstract: To improve endoscopic recognition of the most frequently encountered urinary stone morphologies for a better aetiological approach in lithiasis by urologists. Materials and MethodsAn expert urologist intraoperatively and prospectively (between June 2015 and June 2018) examined the surface, the section, and the nucleus of all encountered kidney stones. Fragmented stones were subsequently analysed by a biologist based on both microscopic morphological (i.e. binocular magnifying glass) and infrared (i.e. Fourier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(71 citation statements)
references
References 24 publications
(34 reference statements)
5
66
0
Order By: Relevance
“…The images used in this contribution (see Table 5) were acquired by an urologist (Dr. Vincent Estrade) who is among the few experts in France able to visually recognize kidney stone types using only in vivo images displayed on a screen during an ureteroscopy. Additionally to this expertise, the annotation of the images used in this work was statistically confirmed in Estrade et al (2020) by a concordance study exploiting the morpho-constitutional analysis of extracted kidney stone fragments (the morpho-constitutional analysis confirmed the visual classification made by the urologist), using microscopy and a Fourier transform infrared spectroscopy (FTIR) analysis, which were exploited as follows.…”
Section: Database Constructionmentioning
confidence: 63%
See 4 more Smart Citations
“…The images used in this contribution (see Table 5) were acquired by an urologist (Dr. Vincent Estrade) who is among the few experts in France able to visually recognize kidney stone types using only in vivo images displayed on a screen during an ureteroscopy. Additionally to this expertise, the annotation of the images used in this work was statistically confirmed in Estrade et al (2020) by a concordance study exploiting the morpho-constitutional analysis of extracted kidney stone fragments (the morpho-constitutional analysis confirmed the visual classification made by the urologist), using microscopy and a Fourier transform infrared spectroscopy (FTIR) analysis, which were exploited as follows.…”
Section: Database Constructionmentioning
confidence: 63%
“…Indeed, despite the variety of compositions and morphologies observed in urinary calculi, about 90% are composed of a limited number of crystalline species and morphological characteristics that are easily recognised through an endoscopic examination Estrade et al (2013Estrade et al ( , 2017. The study in Estrade et al (2020) showed a high concordance between endoscopic and microscopic typing of the kidney stones. More precisely, the concordance of the results was observed in 86.1% of the type I kidney stones, in 85% of the type II kidney stones, in 91% of the type III kidney stones and in 79% of type IV kidney stones made of calcium phosphate.…”
Section: Database Constructionmentioning
confidence: 89%
See 3 more Smart Citations